The aquatic context of Caisteal Ormacleit, South Uist, Outer Hebrides: Lady Penelope’s chateau and its canals - Angus, Stewart (Proceedings of the Society of Antiquaries of Scotland, 2018)
Caisteal Ormacleit [Ormiclate Castle], on the west side of South Uist, was constructed in the early 18th century by Clanranald for his wife Penelope, reputedly in the style of a French chateau, incorporating building materials imported from or via the east coast of South Uist at a time when there were neither roads nor carts. This high-status building (arguably more a fine house than a castle) and its origins and construction are reviewed in the context of historical sources, geology and topography. The history of the building and that of the couple for whom it was built had close associations with the Jacobite battles of 1689 (Killiecrankie) and 1715 (Sheriffmuir). The possible canal sections are reviewed in detail and a convincing case is provided for the existence of a canal network between the east coast of the Uists and the western situation of Caisteal Ormacleit, linking the Olaidh lochs, thus confirming the local tradition that the inland lochs of the Uists were used for boat-based transport and supporting the case for the existence of a wider navigable network within the Uist interior. Past intervention in water management has to be investigated in order to plan for future climate change impacts, and the Olaidh network is reviewed in this context.